Comprehensive Analysis of TRIM Family Genes in Hepatitis Virus B-Related Hepatoma Carcinoma - Hu, Wei; Liu, Dongsheng; Li, Renjie; Qian, Hong; Qiu, Wei; Ye, Qingwang; Kong, Fanyun (Frontiers in Genetics, 2022)
Background: As significant components of E3 ligases, the tripartite motif (TRIM) proteins participate in various biological processes and facilitate the development of several diseases. Nevertheless, the correlations of TIRMs with hepatitis B virus (HBV)-positive hepatoma carcinoma (HCC) are not well elaborated. Methods: The expression profile of TRIM genes in HBV-associated HCC and related clinical information were extracted from the Cancer Genome Atla (TCGA) database and the International Cancer Genome Consortium (ICGC) database. Dependent on the ConsensusPathDB and STRING databases, the gene ontology, Reactome pathways, and protein-protein interaction were assessed. Relied on TIMER 2.0 database, the relationship of the TRIMs with immune infiltration was investigated. Using multivariate analysis and Kaplan Meier analysis, the association between TRIM genes and the prognostic value was examined. Results: A total of 17 TRIM genes, including TRIM16, TRIM17, and TRIM31 with fold change no less than 1.5, were discovered to upregulate in HBV-associated HCC in both TCGA and ICGC cohorts. Relied on gene enrichment analysis, the identified TRIMs were observed to not only be related to the interferon and cytokine signaling but also linked to the adaptive immune system. Particularly, the co-expression patterns of identified TRIMs with other E3 ligase genes and many innate immune genes that are associated with Toll-like receptor signaling, apoptosis, and SUMOylation. Besides, some of identified TRIM expressions were also linked to the infiltration levels of T cells and B cells. Additionally, several TRIM genes were associated with various clinical factors and relevant to the poor survival of HBV-associated HCC. Conclusion: Our findings could deepen our understanding of TRIMs and their correlations with HBV-associated HCC. Furthermore, some of these TRIMs may be utilized as new prognostic markers of HBV-related HCC prognosis, or act as potential molecular targets for the disease.